Revitalization of the Gendang Binge as Identity Karo Langkat Arts - Adina Sembiring; Uyuni Widiastuti; Hendy Obed Sembiring; Ewin Johan Sembiring; Eben Haezarni Telaumbanua (BIRCU, 2022)
The revitalization of the Gendang Binge was carried out due to the loss of the main function of the Gendang Binge in traditional Karo Langkat arts due to the dominant influence of the keyboard in various traditional ceremonies in the Karo Langkat community. The drums of Binge are made of old jackfruit wood which is dried first so that the sound of the drums does not change after the skin is attached. The Binge drum is divided into 2 types, namely the Indung drum and the children's drum. Gendang Binge indung is 19 cm long, with a top cover of 12.5 cm and a bottom cover of 6.5 cm, while the drum for children is 19 cm long, with a top cover of 10 cm and a bottom cover of 8 cm. The material used for the membrane or skin for the Binge drum is napuh skin (a type of endemic animal rabbit) in the Karo highlands, while to tie the skin to the wood used cowhide and for sticks using kaffir lime wood. Some of the techniques in playing Gendang Binge include: Tang and Tih are used to produce the sound of the Gendang Binge ovary, while for Tang and Cek to produce the sound character of the children of Gendang Binge. To produce Tang in the ovary of the Gendang Binge, the large stick must be struck on the edge of the drum, while for Tih the large stick is struck right in the middle of the membrane of the Gendang Binge. To produce a Tang sound from the child's Gendang Binge, the stick is hit on the edge of the lips and must hit the membrane, while to produce a Check sound, the drum stick is hit and pressed at the same time in the middle of the membrane.